2012
DOI: 10.1002/chem.201201239
|View full text |Cite
|
Sign up to set email alerts
|

β‐Cyclodextrin Duplexes That Are Connected through Two Disulfide Bonds: Potent Hosts for the Complexation of Organic Molecules

Abstract: New tubular host molecules, which are composed of two β-cyclodextrin macrocycles that are connected through two disulfide bonds, have been prepared by the air-promoted oxidation of 6(I),6(IV)-dideoxy-6(I),6(IV)-disulfanyl-β-cyclodextrin in aqueous solution. This reaction leads to three products: monomeric intramolecular disulfide and two dimeric species, which are termed as "non-eclipsed" and "eclipsed" cyclodextrin duplexes. Oxidation at a concentration of the starting thiol of 0.1 mM gave the intramolecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Their separation by HPlC could not be achieved under similar conditions as for non-methylated analogues (4). Interestingly, the analogous perallylated duplex was present as a single isomer 16 or 18; however, we were unable to attribute the one of the two possible structures to the product by means of NMr analysis.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Their separation by HPlC could not be achieved under similar conditions as for non-methylated analogues (4). Interestingly, the analogous perallylated duplex was present as a single isomer 16 or 18; however, we were unable to attribute the one of the two possible structures to the product by means of NMr analysis.…”
Section: Introductionmentioning
confidence: 72%
“…We found that the distribution of resulting monomeric and dimeric species is highly influenced by the reaction conditions -the solvent system in particular. First we applied conditions that were similar to our recently published reports on non-alkylated cyclodextrin duplexes (2,4,5). Air oxidation of the disulfanyl derivative 11 was performed at 1 and 10 mM concentrations of compound 11 in the mixture of ethanol/H 2 O (1:1) using ammonium bicarbonate buffer at pH 9.…”
Section: Synthesismentioning
confidence: 96%
See 2 more Smart Citations
“…We have recently described the syntheses and properties of new host systems composed of two α-CD or β-CD macrocycles linked with disulfide bonds. 25,26,[29][30][31] These tube-like molecules showed unusually high binding affinities (K a up to 10 10 M −1 ) to various organic compounds from hydrophobic α,ω-alkanediols 25,26 to fairly hydrophilic medium-sized molecules such as imatinib. 31 Now, we have turned our attention to a larger γ-CD homologue.…”
Section: Introductionmentioning
confidence: 99%